Acute‐phase glycoprotein N‐glycome of ovarian cancer patients analyzed by CE‐LIF. Issue 11 (17th February 2016) - Weiz, Stefan; Wieczorek, Marta; Schwedler, Christian; Kaup, Matthias; Braicu, Elena Iona; Sehouli, Jalid; Tauber, Rudolf; Blanchard, Véronique
Abstract : Epithelial ovarian cancer (EOC) is the most frequent cause of death from all gynecological malignancies because of its late diagnosis. As N ‐glycosylation is modified in the course of ovarian cancer, it is a promising source of tumor biomarkers. In this work, serum glycoproteins, depleted from albumin and IgG, were separated by 2DE. Protein spots of acute‐phase proteins were identified by peptide mapping and their corresponding glycan moieties were released enzymatically, fluorescently labeled and analyzed by CE‐LIF. In the positive acute‐phase proteins, haptoglobin, α1‐antitrypsin, and α1‐antichymotrypsin, an increase of antennarity and Lewis X motif could be measured in EOC patients on tri‐ and/or tetraantennary N ‐glycans. Tetraantennary N ‐glycans containing three Lewis X epitopes and triantennary N ‐glycans containing a β(1‐6) branch and a Lewis X epitope were only present in EOC patients. We also showed for the first time that the core‐fucosylated biantennary digalactosylated N ‐glycan of α1‐acid glycoprotein is a potential biomarker for EOC. To conclude, core‐fucosylated biantennary N ‐glycans on α1‐acid glycoprotein as well as higher antennarity and increased amounts of Lewis X motif on haptoglobin, α1‐antitrypsin, and α1‐antichymotrypsin are promising biomarkers for EOC. Nevertheless, their specificity and selectivity for the early detection of EOC should be evaluated in a larger study.